Optimasi Kinerja Karyawan Melalui Sinergi Dukungan Supervisi Dan Kepuasan Kerja - Didit Darmawan; Arif Rachman Putra; Misbachul Munir; Eli Retnowati; Tri Seno Anjanarko (Global Leadership Organizational Research in Management, 2023)
This study aims to analyze the effect of supervision support and job satisfaction on employee performance. The research approach used is quantitative by involving 100 respondents from one of the companies in the area in Sidoarjo City, using the saturated sampling method. Data were collected through a questionnaire with a 5-point Likert scale, and statistical analysis was conducted using multiple linear regression. The results showed that both independent variables, namely supervisory support and job satisfaction, have a significant influence on employee performance. Multiple linear regression analysis shows that changes in the level of supervisory support and job satisfaction are positively correlated with increases in employee performance. These findings can serve as a foundation for companies in improving human resource management strategies to increase employee productivity and well-being. Using a quantitative approach, this study makes a positive contribution to the human resource management literature, as well as offering practical solutions for companies in achieving their organizational goals.